The history and development of newspaper electronic pagination systems in the United States, 1975-1987 - Beyrouti, Nouri (1990)
The advancement of pre-press production technologies since the invention of Mergenthaler's linotype line-caster has been remarkable, and its effect on the daily newspaper industry, similarly impressive. Even Mergenthaler's device was a revolutionary improvement in speed over the traditional flat platen press developed by Gutenberg several centuries earlier. The development of new technologies over the centuries has periodically brought new waves of progress. Each of these revolutions has changed irrevocably the speed and complexity with which knowledge is assimilated and distributed by societies. The present study traces the historical development of the latest wave of technological advances, beginning with the advent of computerized text entry in the early 1970's and developing towards complete computer-to-plate production of a newspaper page, or pagination. Though this goal has yet to be fully realized, the technology involved continues to grow, and the advancement of computer technology that has occurred especially during the 1980s, has helped that end. The study is divided into six chapters. Chapter I is an introduction to the study and the terminology involved, as well as the major questions asked by the study. Chapter II reviews the history of printing from ancient times, to Gutenberg's invention of movable type, through Mergenthaler's line-casting machine, to the invention of cold type processes in the 1940s. Chapters III and IV discuss the development of pagination from the early 1970s to the present time (about 1987). These sections trace the growth of pagination techniques that grew up around front end processes and more lately back end processes have also been developed successfully. Chapter V analyzes survey data taken from representatives from daily newspapers who use pagination systems. These respondents gave their perceptions of how pagination worked at their paper and how they view the prospects of pagination for the future. Chapters V and VI discuss the responses of the survey respondents in relation to the whole study. One of the findings of the survey was that survey respondents felt that while pagination was a vast improvement over old methods (hot type), it did not necessarily bring vast improvements in cost and speed over cold type processes that were already in place. This was perhaps, due to the unevenness with which the total pagination process has developed, and the continuing problems involved in merging line-art and graphics with text. Increased computer storage space and other advances may solve this problem soon, and satellite transmission of graphic art for national advertisements, to specific newspapers is a new development being planned for the near future.